2012
DOI: 10.1093/chemse/bjr121
|View full text |Cite
|
Sign up to set email alerts
|

Modulation by Octopamine of Olfactory Responses to Nonpheromone Odorants in the Cockroach, Periplaneta americana L.

Abstract: Olfactory receptor cells in insects are modulated by neurohormones. Recordings from cockroach olfactory sensilla showed that a subset of sensory neurons increase their responses to selected nonpheromone odorants after octopamine application. With octopamine application, recordings demonstrated increased firing rates by the short but not the long alcohol-sensitive sensilla to the nonpheromone volatile, hexan-1-ol. Within the same sensillum, individual receptor cells are shown to be modulated independently from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 57 publications
4
19
0
1
Order By: Relevance
“…Grooming as nonspecific mechanism of signal cleanup is probably a widespread phenomenon; it was noticed in different insect species challenged with pheromone and nonpheromone odors [3941]. Our present data shows that eucalyptol, the general odorant which causes excitation of a receptor cell housed in male-specific pheromone-sensitive antennal sensilla [30, 42] induces significant changes in the frequency of antennal grooming.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Grooming as nonspecific mechanism of signal cleanup is probably a widespread phenomenon; it was noticed in different insect species challenged with pheromone and nonpheromone odors [3941]. Our present data shows that eucalyptol, the general odorant which causes excitation of a receptor cell housed in male-specific pheromone-sensitive antennal sensilla [30, 42] induces significant changes in the frequency of antennal grooming.…”
Section: Discussionmentioning
confidence: 55%
“…The setup consisted of 3 components: a transparent plastic cage (30 × 45 × 30 cm) containing food and water, a shelter (17.0 × 17.0 × 5.5 cm) that was constantly dark inside, and an exchangeable test chamber (20 × 20 × 8 cm); the latter 2 were separated from the cage with plastic doors (modified from [30]). At the beginning of testing, the door between the shelter and the cage was shut, and the door between the cage and test chamber was open for a short time, allowing only one insect to enter in it.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Melatonin also appears to exert neuromodulatory effects in insects 54, 55 . Interestingly, many of these amines modulate the olfactory system 5658 .…”
Section: Discussionmentioning
confidence: 99%
“…We observed that antennae of the American cockroach, Periplaneta americana (Linnaeus) (Blattodea, Blattidae), that were immobilized for electrophysiological studies, accumulated a shiny substance on their surface (18). We hypothesized that grooming might serve to remove these excess native secretions and compared groomed and nongroomed antennae of male P. americana cockroaches using field emission gun scanning electron microscopy (FEG SEM).…”
mentioning
confidence: 99%